2018
DOI: 10.1161/circulationaha.117.030353
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Chondroitin Sulfate Glycosaminoglycans to Treat Cardiac Fibrosis in Pathological Remodeling

Abstract: CS glycosaminoglycans accumulate during cardiac pathological remodeling and mediate myocardial inflammation and fibrosis. rhASB targets CS effectively as a novel therapeutic approach for the treatment of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 67 publications
1
45
1
Order By: Relevance
“…Overexpression of ARSB was able to reverse the inhibitory effect of DHT on DKK3 expression in PEC (Figure G). Multiple studies have shown the impact of DKK3 inhibition on Wnt signaling, with subsequent impact on proliferation and remodeling pathways …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of ARSB was able to reverse the inhibitory effect of DHT on DKK3 expression in PEC (Figure G). Multiple studies have shown the impact of DKK3 inhibition on Wnt signaling, with subsequent impact on proliferation and remodeling pathways …”
Section: Discussionmentioning
confidence: 99%
“…Increases in chondroitin sulfate and the chondroitin sulfate proteoglycan versican were identified in more aggressive prostate cancers . Increased C4S has significant consequences for transcription, signaling, metabolism, and proliferation in the prostate and in other tissues …”
Section: Introductionmentioning
confidence: 99%
“…In areas more distant from the surface of the cells, chondroitin-and dermatan sulfate-containing proteoglycans (CSPGs and DSPGs respectively) predominate 151 . In both human patients with heart failure and in animal models of myocardial disease, CSPGs accumulate in fibrotic regions 152 . The ECM in the pressure-overloaded heart is also enriched with a wide range of small leucine rich proteoglycans (SLRPs), such as biglycan, decorin, fibromodulin, lumican and osteoglycin.…”
Section: Matricellular Proteinsmentioning
confidence: 99%
“…The preceding descriptions regarding inflammation and therapeutic pathways using GAGs are equally applicable to CAD, also known as coronary heart disease, and to other cardiovascular diseases. Studies have found that countering the degradation of GAGs, in particular the accumulation of CS/DS in myocardial cells, is a major therapeutic pathway for several cardiovascular diseases [ 48 , 123 , 124 ].…”
Section: Xylose/xylitol Hypertension Acute Kidney Injury Coronary mentioning
confidence: 99%